Assessing performance of modern Brillouin spectrometers - Coker, Zachary; Troyanova‐Wood, Maria; Traverso, Andrew J.; Yakupov, Talgat; Utegulov, Zhandos; Yakovlev, Vladislav V. (Optics Express, 2018)
Brillouin spectroscopy and imaging has experienced a renaissance in recent years seeing vast improvements in methodology and increasing number of applications. With this resurgence has come the development of new spontaneous Brillouin instruments that often tout superior performance compared to established conventional systems such as tandem Fabry-Perot interferometers (TFPI). The performance of these new systems cannot always be thoroughly examined beyond the scope of the intended application, as applications often take precedence in reports. We therefore present evaluation of three modern Brillouin spectrometers: two VIPA-based spectrometers with wavelength-specific notch filters, and one scanning 6-pass TFPI. Performance analysis is presented along with a discussion about the dependence of measurements on excitation laser source and the various susceptibilities of each system.